Measurement of pulse wave velocity in normal ageing: comparison of Vicorder and magnetic resonance phase contrast imaging. Issue 1 (December 2016) - Parikh, Jehill; Hollingsworth, Kieren; Kunadian, Vijay; Blamire, Andrew; MacGowan, Guy
Abstract Background Pulse wave velocity is an important measure of cardiovascular risk, and can be measured by several different techniques. We compared age-related changes in pulse wave velocity derived from carotid and femoral artery waveforms using the Vicorder device and descending thoracic aorta time velocity curves using phase contrast magnetic resonance imaging (MRI) in a group of normal healthy volunteers, without cardiovascular disease, aged between 20 and 79 years. Methods Eighty subjects underwent same-day measurements of Vicorder and MRI pulse wave velocity measurements. Results Both Vicorder and MRI-based pulse wave velocity measurements were significantly increased with age (R  = 0.59 and 0.57 respectively, bothP  < 0.0001). Vicorder and MRI pulse wave velocities were also significantly related to each other (R  = 0.27, P  < 0.05), and Bland Altman plots showed that on average Vicorder measurements were 1.6 m/s greater than MRI. In 5 % of cases, agreement between the values of the two techniques were above and below 2 standard deviations, and these were at higher levels of pulse wave velocities. Multiple linear stepwise regression analysis confirmed highly significant relationships of both techniques to age (bothP  < 0.0001), and MRI was also significantly related to heart rate (P  = 0.006) but Vicorder was not. Conclusions Both Vicorder and MRI perform similarly in detecting age-related changes in pulse wave velocity. Thus, the choice of using one or the other will depend on other aspects of the investigation, such as the need for portability favouring Vicorder, or need for additional cardiovascular imaging favouring MRI. Trial registration ClinicalTrials.Gov identifierNCT01504828